Use of the FINDRISC scale in the department of Cundinamarca, Colombia: A descriptive and cross-sectional study - Ramon A Castaño; Maria Angélica Granados; Angel F Maestre; Juan Felipe Trujillo-Angel; Constanza Neri Morales; Carlos Leal Bernal; Carlos Julio Corzo Diaz; Juan Pablo Bernal Soler; Natalia Trujillo; Juan Sebastian Cardona; Rossmary Gonzalez; Maria Alejandra Larrarte; et al. (Revista Colombiana de Endocrinología, Diabetes y Metabolismo)
Background: Type II diabetes (T2D) is a chronic disease with high rates of morbidity and mortality, which implies a great impact on the economy and health systems due to its high prevalence rates, complications, and costs. Prediabetes arises as an abnormal state that precedes type II diabetes and is associated with multiple risk factors. Therefore, strategies such as the FINDRISC survey have emerged to identify people at risk of developing prediabetes and type II diabetes as early as possible.